FAKTOR-FAKTOR YANG MEMPENGARUHI PENGAMBILAN KEPUTUSAN PEMBELIAN PRODUK REI OUTDOOR GEAR DI BANDAR LAMPUNG - Irvan Baskara; Lestari Wuryanti; Iing Lukman (Sekolah Tinggi Ilmu Ekonomi Rahmaniyah Sekayu, 2022)
This study aims to test and prove the factors affecting decision to purchase rei outdoor gear product in Bandar Lampung. Thepopulation in this study is the sales volume of rei outdoor gear product in Bandar Lampung from 2017-2018 amounting to 30.484 .sales of sampling methods using purposive sampling with a number of respondent 400 people. sampling criteria, namely consumers who have purchased rei outdoor gear product in Bandar Lampung. The variables used are as many as 5 variables. The test equipment used was a partial tes. Test result show that.a) the store atmosphere variable has no effect on purchasing decision. b) Locaton variables do not affect purchasing decision. c) Motivation variable does no affect purchasing decisions. d) Perception variable does not affect purchasing decisions. e) Product quality variable does not affect the purchase decision.